2014
DOI: 10.1016/j.bbr.2014.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Effect size of memory deficits in mice with adult-onset P301L tau expression

Abstract: Transgenic mice expressing mutations in tau have yielded essential discoveries for Alzheimer’s disease. One of the most commonly used tau mouse models is the tet-off Tg(tauP301L)4510 model that expresses P301L human tau driven by the calcium-calmodulin kinase IIα (CaMKIIα) promoter system. Tau expression in this model is regulatable, allowing for suppression of mutant tau expression until adulthood and prevention of possible developmental alterations resulting from P301L tau expression during development. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Considering the LR deficit observed here and the fact that spatial deficits have been reported in these mice at younger ages (Murakami et al., ), future studies of this model should prioritize early detection of hippocampus‐dependent deficits. For example, there is some evidence that mice expressing the P301L transgene are particularly impaired in trace fear conditioning relative to other hippocampal‐dependent tasks such as the MWM (Hunsberger et al., ); thus, researchers using TgTau P301 mice might consider employing trace fear conditioning tasks to detect the earliest memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the LR deficit observed here and the fact that spatial deficits have been reported in these mice at younger ages (Murakami et al., ), future studies of this model should prioritize early detection of hippocampus‐dependent deficits. For example, there is some evidence that mice expressing the P301L transgene are particularly impaired in trace fear conditioning relative to other hippocampal‐dependent tasks such as the MWM (Hunsberger et al., ); thus, researchers using TgTau P301 mice might consider employing trace fear conditioning tasks to detect the earliest memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…At 2.5 months of age, while still on DOX to suppress tau expression, mice underwent behavioral testing in the water radial arm maze (WRAM) to establish that cognitive deficits were dependent upon tau expression as previously described (Hunsberger et al 2014b) ( Fig. 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…However, it was recently shown that neuronal firing patterns are altered as early as 5 months of age, leading to the suggestion that perturbations in coordinated synaptic activity may occur in early-stage pathology (Menkes-Caspi et al., 2015). Most importantly, deficits in cognitive function seem to emerge in advance of major histopathology (Hunsberger et al., 2014), as suggested for dementia (Sperling et al., 2011). Therefore, pursuing the hypothesis that synaptic dysfunction is an early harbinger of dementia, we have determined when and how changes in synapse number are first manifested in rTg4510 mice.…”
Section: Introductionmentioning
confidence: 99%